2016
DOI: 10.2337/diaspect.29.3.146
|View full text |Cite
|
Sign up to set email alerts
|

Challenges With Insulin in the Inpatient Setting

Abstract: IN BRIEF This article reviews potential challenges to and necessary considerations for ensuring the safe and effective use of insulin in the hospital setting. It offers practical suggestions for managing insulin-related issues regarding medication reconciliation, general inpatient management, and the use of concentrated insulin products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Insulin is frequently cited as one of the medicines most commonly associated with medication errors in hospital, and is widely used to treat diabetes within the inpatient setting . As the prevalence of diabetes continues to increase (more than one million people with diabetes were admitted to hospital in England in 2017), along with the range of available insulins in varying concentrations, the challenge of diabetes management in people in hospital persists, with potentially greater scope for insulin errors .…”
Section: Introductionmentioning
confidence: 99%
“…Insulin is frequently cited as one of the medicines most commonly associated with medication errors in hospital, and is widely used to treat diabetes within the inpatient setting . As the prevalence of diabetes continues to increase (more than one million people with diabetes were admitted to hospital in England in 2017), along with the range of available insulins in varying concentrations, the challenge of diabetes management in people in hospital persists, with potentially greater scope for insulin errors .…”
Section: Introductionmentioning
confidence: 99%
“…This reactive approach has been found to inadequately take into account the amount of carbohydrate in the meal to be consumed as well as various other patient-specific factors; failing to consider these factors may lead to further episodes of hyperglycemia and hypoglycemia. 10 Additionally, the results of the Randomized Study of Basal-Bolus Insulin Therapy in the Inpatient Management of Patients With Type 2 Diabetes (RABBIT 2 trial) found basal-bolus insulin therapy to achieve the blood glucose target in 68% of patients compared to 38% in the sliding-scale regular insulin group, further invalidating prior correctional scale-only approach. 11 Finally, a lack of reporting of hypoglycemia occurrences and oversight resulted in the inability for diabetes specialists to track quality metrics and prospectively plan interventions.…”
Section: Hospital-wide Initiativesmentioning
confidence: 99%